Rendahnya Penggunaan Bahasa Sumba Timur di Kalangan Remaja dalam Berinteraksi di KotaWaingapu-Sumba Timur (NTT) - Upa Raji, Rambu; Zuryani, Nazrina; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
The language of East Sumba has speakers below 1000 people in 2002, the use of regional languages in Waingapu city is very low, especially among teenagers. This research uses qualitative method with Levi-Strauss approach that there is dynamism of linguistic sign language (Langue) that impact on individual speech (Parole) with observation data, interview, Focus Group Discussion (FGD), and Documentation. The technique of data analysis is done descriptively qualitative and interpretative. The results of the study indicate that: (1) The low use of East Sumba language among adolescents resulting from heterogeneous communities, low education, inter-ethnic marriage, and the shame of using local language in Waingapu city (2) There is no specific learning process in understanding East Sumba language; the youth learn ten language of East Sumba from the parents so that individual speech as adolescents who interact actively to the exclusion of local language. Local government constraints have not conducted local language learning in schools due to the scarcity of regional language teachers. (3) The low use of East Sumba language causes the loss of greetings to the nobility, the changing social order, and the loss of traditional songs dance. Key Words : Usage, East Sumba Language, adolescent, Social Interactions